Perspective SPILSS Models for Analyzing the Development of Paragliding Athletes in Central Java - Listiarini, Dian; ‎ , Muhlisin; Kurniawan, Rian; Paramitha, Sandey Tantra (KnE Social Sciences, 2024)
The purpose of this study was to use the Sports Policy Factors Leading to International Sporting Success (SPLISS 2.0) instrument and the nine pillars of elite sports success approach to survey and assess the success factors of coaching. Athletes from eight districts or cities in Central Java that had paragliding organizations, as well as chairs, secretaries, treasurers, and coaches were included in the survey. Data were analyzed through SPLISS 2.0 reports and quantitative analysis methods. Potential success factors were determined quantitatively using 96 CSFs assigned to a score of 0–1 based on nine pillars. Findings show that Banyumas, Grobogan, the Semarang district, and Karanganyar are the four regions offering the highest numbers of paragliding sports. The districts of Grobogan and Semarang are best in participation, talent identification, and talent development. The results show that many regions have yet to adopt the nine pillars. It is intended that each region would produce paragliding athletes of the highest caliber, honoring Central Java and Indonesia as a country. Keywords: SPLISS models, paragliding, sport policy